Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pbio.1002540
|View full text |Cite|
|
Sign up to set email alerts
|

Resource Availability Modulates the Cooperative and Competitive Nature of a Microbial Cross-Feeding Mutualism

Abstract: Mutualisms between species play an important role in ecosystem function and stability. However, in some environments, the competitive aspects of an interaction may dominate the mutualistic aspects. Although these transitions could have far-reaching implications, it has been difficult to study the causes and consequences of this mutualistic–competitive transition in experimentally tractable systems. Here, we study a microbial cross-feeding mutualism in which each yeast strain supplies an essential amino acid fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(237 citation statements)
references
References 37 publications
10
207
0
Order By: Relevance
“…Well-mixed suspension cultures have the disadvantage that species with widely differing growth rates cannot be co-cultured without engineering artificial dependencies such as amino acid cross feeding between the species [56]. Natural microbial communities have evolved numerous mechanisms for ensuring species coexistence, most notably the biofilm mode of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Well-mixed suspension cultures have the disadvantage that species with widely differing growth rates cannot be co-cultured without engineering artificial dependencies such as amino acid cross feeding between the species [56]. Natural microbial communities have evolved numerous mechanisms for ensuring species coexistence, most notably the biofilm mode of growth.…”
Section: Discussionmentioning
confidence: 99%
“…A study using amino-acid-auxotrophic yeast strains demonstrated that changes in amino acid availability can modulate the types of interaction between species. Depending on the resource availability, the interaction of these strains changed from obligatory and facultative mutualism to competition and parasitism 69 . Unravelling these dependencies and the resulting dynamic interactions of members in a community would be of great importance for microbiome research.…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…Notably, by adjusting amino acid concentrations, Hoek et al . recently altered the relationship between two yeast strains through several distinct outcomes from obligate mutualism to competitive exclusion (Hoek et al ., ).…”
Section: Discussionmentioning
confidence: 97%